Penggunaan Algoritma K-Means Berbasis Website dalam Menentukan Kelompok Pembinaan Al-Qur’an di Pondok Pesantren Islamiyah Syafiiyah Sumberanyar - Rahman, Zainur; Yaqin, Moh Ainol; Syafiih, M (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This study aims to develop a web-based application system using the K-Means algorithm to cluster students in Al-Quran training at Pondok Pesantren Islamiyah Syafi’iyah Sumberanyar, Paiton, Probolinggo. The system is designed to improve efficiency and accuracy in determining training groups based on students' Quranic reading skills, including Tajwid, fluency, and memorization. By analyzing data from 824 students, this research successfully classifies them into three skill categories: "Ulya" (advanced), "Wustha" (intermediate), and "Ula" (beginner). This clustering process provides an objective guide for assigning students to appropriate training groups and supports the personalization of the learning process. Additionally, the implementation of web-based technology facilitates easier data management and greater accessibility for administrators. The results show that the K-Means algorithm significantly enhances the efficiency and accuracy of the training process compared to manual methods. These findings are not only relevant to this pesantren but also have the potential to be applied to other Islamic educational institutions to optimize training management.